Radiotheranostic Agents in Hematological Malignancies - Caers, Jo; Duray, Elodie; Vrancken, Louise; Marcion, Guillaume; Bocuzzi, Valentina; De Veirman, Kim; Krasniqi, Ahmet; Lejeune, Margaux; Withofs, Nadia; Devoogdt, Nick; Dumoulin, Mireille; Karlström, Amelie Eriksson; et al. (Frontiers in Immunology, 2022)
Radioimmunotherapy (RIT) is a cancer treatment that combines radiation therapy with tumor-directed monoclonal antibodies (Abs). Although RIT had been introduced for the treatment of CD20 positive non-Hodgkin lymphoma decades ago, it never found a broad clinical application. In recent years, researchers have developed theranostic agents based on Ab fragments or small Ab mimetics such as peptides, affibodies or single-chain Abs with improved tumor-targeting capacities. Theranostics combine diagnostic and therapeutic capabilities into a single pharmaceutical agent; this dual application can be easily achieved after conjugation to radionuclides. The past decade has seen a trend to increased specificity, fastened pharmacokinetics, and personalized medicine. In this review, we discuss the different strategies introduced for the noninvasive detection and treatment of hematological malignancies by radiopharmaceuticals. We also discuss the future applications of these radiotheranostic agents.